(572) La Politique Conjoncturelle en Economie Ouverte السياسة الاقتصادية في الاقتصاد المفتوح - Salin, Pascale (معهد التخطيط القومى, 2024)
In May 1964, the International Monetary Fund granted a standby credit of $40 million to the United Arab Republic to support its economic stabilization program. The program aimed to prevent public financing of development plans from causing inflationary pressures that could disrupt the balance of payments, potentially necessitating restrictive measures like import reduction, jeopardizing the plan's implementation. The country's external revenues largely depended on a single export product, making its balance of payments and domestic activity highly vulnerable to price or production fluctuations. Hence, measures were needed to balance external payments and mitigate the internal impacts of these economic fluctuation